A Correlation Study Between Students’ Grammar Mastery and Writing Ability in The Second Semester Students of The English Education Study Program - Mesah, Murni Yunita; Tamelan, Thersia Magdalena; Ludji, Ifoni (English Education Study Program - Artha Wacana Christian University, 2024)
Writing requires learners to articulate their thoughts and ideas in a coherent and organized manner. Understanding grammar can help students organize their thoughts in sentences that readers can easily understand. This study, title